2020
DOI: 10.3390/cancers12020344
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Hyperprogressive Disease in Non-Small Cell Lung Cancer by Monitoring of Systemic T Cell Dynamics

Abstract: Hyperprogressive disease (HPD) is an adverse outcome of immunotherapy consisting of an acceleration of tumor growth associated with prompt clinical deterioration. The definitions based on radiological evaluation present important technical limitations. No biomarkers have been identified yet. In this study, 70 metastatic NSCLC patients treated with anti-PD-1/PD-L1 immunotherapy after progression to platinum-based therapy were prospectively studied. Samples from peripheral blood were obtained before the first (b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 26 publications
0
91
0
Order By: Relevance
“…Further analysis revealed that these highly differentiated CD4 + T cells were mainly composed of non-exhausted memory (CD45RA − CD62L +/− ) CD4 cells, which significantly affect T cell proliferation response during immunotherapy ( 47 ). Subsequently, this research team conducted a prospective study in 70 NSCLC patients treated with ICIs, indicating that HPD was closely associated with dysfunctional CD4 immunity and an increased number of peripheral CD28 − CD4 + T cells ( 48 ). Julia et al also highlighted the importance of functional CD4 T cell immunity for anti-tumor response, and they observed higher baseline proportion of central memory CD4 + T cells in responders ( 40 ).…”
Section: Circulating Immune Cell Subsetsmentioning
confidence: 99%
“…Further analysis revealed that these highly differentiated CD4 + T cells were mainly composed of non-exhausted memory (CD45RA − CD62L +/− ) CD4 cells, which significantly affect T cell proliferation response during immunotherapy ( 47 ). Subsequently, this research team conducted a prospective study in 70 NSCLC patients treated with ICIs, indicating that HPD was closely associated with dysfunctional CD4 immunity and an increased number of peripheral CD28 − CD4 + T cells ( 48 ). Julia et al also highlighted the importance of functional CD4 T cell immunity for anti-tumor response, and they observed higher baseline proportion of central memory CD4 + T cells in responders ( 40 ).…”
Section: Circulating Immune Cell Subsetsmentioning
confidence: 99%
“…In our particular NSCLC cohort, a low baseline percentage of memory CD27-CD28-CD4 T cells correlated with intrinsic resistance (Zuazo et al, 2019). Moreover, a sudden increase in highly differentiated CD4 T cells (CD4 T HD burst) following the first cycle of immunotherapy was indicative of hyperprogressive disease (Zuazo et al, 2018;Arasanz et al, 2020). The identification of hyperprogressors is also of the outmost importance, as these patients deteriorate very quickly with fatal outcomes.…”
Section: Resultsmentioning
confidence: 85%
“…For ovarian cancer, retrospective analysis of data from a clinical trial with a cohort of 89 patients that received ICB showed that over half of the patients (N = 46, 51.6%) experienced early treatment discontinuation (≤12 weeks after treatment initiation) due to radiographic or clinical disease progression ( 122 ). The biological basis and mechanisms underlying HPD, such as the Fc region of antibodies ( 123 ), EGFR and MDM2/MDM4 amplification ( 123 ), and senescent CD4+ T cells ( 124 ), are being clarified. This phenomenon has polarized oncologists, who debate whether this effect could still reflect the natural history of the disease.…”
Section: Challenges and Future Developmentsmentioning
confidence: 99%